Labuan Financial Service Authority (Labuan FSA) impact reinsurance company’s profit in Malaysia / Noor Atikah Kadir - Kadir, Noor Atikah (Faculty of Business and Management, 2010)
The insurance involves three parties operating the business. It is including the primary insurance, intermediaries and reinsurance. The main functions of reinsurance are to retain the large premium risk, spread the hazardous risk and the fluctuation of the annual aggregate claims experience by the primary insurer. (Carter, Reinsurance: The Purpose of the Reinsurer, 1979) In some countries, the reinsurance practiced by two way of business which are offshore and inshore authority. Basically, in the inshore regulation, the reinsurance company imposed all the rules and taxes. An offshore enjoyed tax-exempt and these companies not authorized to engage in business in the constituting jurisdiction. Bermuda Island, Cayman Island and Labuan Island are some example for offshore authority island in the insurance business. There are about 10 reinsurance companies in Malaysia before Malaysia Reinsurance Berhad (Malaysian Re) was formed in 1972. Next, Bank Negara Malaysia (BNM), the body that regulates, authorize and supervise all the insurance-based companies in Malaysia announced the fixed rates of certain business portfolio compulsory to be retain to Malaysian Re. As a result, the market share of other reinsurance drops drastically. Some of this reinsurance surrendered their license while some registered under Labuan Financial Service Authority (Labuan FSA). Therefore, only five (5) reinsurance left in Malaysia. It includes Munich Reinsurance, Toa Reinsurance, Swiss Reinsurance, Hannover Reinsurance as well as Malaysian Re. On 2006, Asia Capital Reinsurance joined the reinsurance business and makes the total reinsurance company to six (6) until now.